Potential of Sugarcane Bagasse as Binder in Treatment of Petroleum Sludge by Using Stabilization/ Solidification Method - Mohd Kamil, Nor Amani Filzah; Noor Azlan Ismail (Recent Trends in Civil Engineering and Built Environment, 2020)
Petroleum sludge is one of the main hazardous wastes generated in the petroleum industry. It is a complex emulsion of various petroleum hydrocarbons and heavy metals. Due to its hazardous characteristics and quantities continuously increased around the world, the effective treatment of petroleum sludge has attracted widespread attention. Proper treatment techniques such as the Stabilization/Solidification (S/S) method have been employed and capable of immobilization of contaminants in leachate. In this study, sugarcane bagasse (SCB) was used partially to reduce the amount of cement in the S/S technique. The objectives were determination the leaching of heavy metals and the strength of the mixture. In the leaching test, concentration for all metals, namely, copper, zinc, chromium, nickel, lead, arsenic, and barium were far below the permissible limit in the USEPA standard. Based on the result, 10% SCB shows the lowest concentration of heavy metals in leachate. In strength performance, the control sample (0% SCB) shows the highest strength. The incorporation of SCB in mixture reduces the strength of the mixture. Only a 5% SCB mixture shows the strength is suitable for landfill disposal. In a conclusion, the SCB was very effective in terms of reducing the leaching concentration. However, in terms of strength SCB was not effective. Thus, it is recommended to include sand, quarry dust or any material which can increase the strength of the mixture in a future study.